Caracterização dos facilitadores para criação de resiliência na cadeia de suprimentos : um estudo de caso a partir das atividades da logística inbound - Costa, Flávio Henrique de Oliveira (Universidade Federal de São Carlos, 2016)
Nowadays supply chains have grown in size and complexity. In this environment, unforeseen events (ruptures) in the flow of goods, services or information can occur unexpectedly, having increasingly significant impacts on companies. Resilience is defined as the ability to prepare, adapt and react to ruptures, thus maintaining operations connected and having control over the structure and functions. Considering this, the activities carried out by inbound logistics may influence creating resilience in the supply chain, mainly by including the flow of materials and supplying the company, which are activities directly affected during the ruptures. However, little is known about how the inbound logistics contribute to creating resilience. Taking this into account, the aim of this study is to identify which resilience enablers there are and how inbound logistics use them to create supply chain resilience. A systematic literature review of resilience and inbound logistics, followed by content analysis defined what the activities of inbound logistics are, which resilience enablers there are in the supply chain and also defined how the activities make use of the enablers. In the next step of the research, a multiple case study of 2 Brazilian dairies was performed. Interviews were transcribed and content analysis was conducted using the QDA Miner software. Case-by-case and cross-case analyses were carried out, observing how different types of rupture can influence the enablers used. Thus, the resilience enablers present in cases were highlighted, and the activities that use them were defined, localized facilitators were, reacting speed, collaboration, communication, supply chain structure, flexibility, risk management, product innovation, contingency planning, redundancy, company's financial health, security technology, cross-functional groups, knowledge management, visibility and supplier quality. Knowledge about the relationship between them enables the companies studied to manage their resources more profitably and extend these practices to their suppliers. It should also be mentioned that the companies studied operate with low inventory levels, therefore other companies in the same situation can use the knowledge gained from this research to administer facilitators in order to recover from ruptures.
Keywords: Cadeia de suprimentos resiliente; Logística inbound; Revisão sistemática de literatura; Facilitadores; Supply chain resilience; Inbound logistics; Systematic literature review; Facilitators; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO